Toward Camden - Romero, Mercy, 1974- (Black outdoors., 2021)
"In Toward Camden, Mercy Romero writes a complex and vibrant story about the largely African American and Puerto Rican Cramer Hill neighborhood in New Jersey where she grew up."--